Determinan Efektivitas Program Komunikasi, Informasi, Edukasi Obat dan Makanan Saat Pandemi Covid-19 - Nurvika Widyaningrum; Made Widdi Ellinda Patra (Eruditio : Indonesia Journal of Food and Drug Safety, 2022)
Consumption of medicines, health supplements, and traditional medicines has increased during the Covid-19 pandemic. People with health complaints prefer self-medication rather than outpatient treatment. The risk of self-medication needs to be balanced with the knowledge and people’s ability to choose safe medicinal products, health supplements, and traditional medicines. FDA (BPOM) increases public awareness related to the safety of drugs and food through an effective Communication, Information, and Education (CIE) program. Demographic factors can influence the awareness level, including knowledge, attitudes, and behavior. This study aims to determine the association between demographic factors and the effectiveness of CIE during the Covid-19 pandemic. The research uses quantitative methods—data collection through online questionnaires. As many as 39,398 respondents were selected through purposive sampling from the CIE audience population throughout Indonesia from June 2020 to June 2021. Data were analyzed using the ANOVA test with SPSS 16 at a significance level of 0.05. The results showed that the CIE effectiveness index was 92.61 (very effective). Demographic factors, namely occupation and education, influence the CIE effectiveness index, but gender and age had no influence. Demographic factors also influence the index of the indicator. Occupation, education, and age are also related to the media variety index. Occupation and education are also associated with the understanding index, age-related to the benefit index, and work, education, and age affect the interest index. The effectiveness of CIE during the Covid-19 pandemic is influenced by demographic factors, namely work, and education. BPOM needs to plan the CIE program by considering demographic characteristics, including education, occupation, and age of the CIE target audience so that the CIE program can be effective.